1966
DOI: 10.1002/app.1966.070100602
|View full text |Cite
|
Sign up to set email alerts
|

Thermal oxidation of thermoplastics

Abstract: SynopsisCommercial thermoplastics may be classified by the types of rate curves obtained on thermal oxidation. The rate of oxidation of an acrylonitrile-butadiene-st.yrene plastic is affected by sample thickness and appears to be diffusion-controlled. Pigmentation increases the reaction rate of this compound in all the cases studied because of the catalytic effect of the metals present.. Carbon black adversely affects the oxidation rate of stabilized polypropylene. The acetal plastics decompose under oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…-In service life degradation It was shown that at oven ageing conditions PC reacts with oxygen although the rates are small [153,154]. The degradation of bisphenol A polycarbonate (PC) in air at 300 °C cause random scission of the polymeric chains.…”
Section: Polycarbonates -Degradation During Processingmentioning
confidence: 99%
“…-In service life degradation It was shown that at oven ageing conditions PC reacts with oxygen although the rates are small [153,154]. The degradation of bisphenol A polycarbonate (PC) in air at 300 °C cause random scission of the polymeric chains.…”
Section: Polycarbonates -Degradation During Processingmentioning
confidence: 99%
“…At higher temperanares the oxygen uptake reaction leading to polymer oxidation shows different behaviour (14). The initial slopes of dV/dt versus (l-X) for 130 ~ and 140 ~ are shown in Figure 4.…”
Section: Results and Disscusionmentioning
confidence: 97%
“…(4) due to the exponential nature of t". The second factor is related to the degradation of ABS by molecular chain breaking, oxidation, and butadiene particle coelescence at the high temperatures used during FD extrusion (Casale et al, 1975;Kelleher, 1966). This temperature related degradation is being confirmed via comparison of the molecular weights and microstructures (i.e., the butadiene particle size distribution) of the bulk ABS with extruded FD-ABS.…”
Section: J/mol • K)mentioning
confidence: 93%